PENGEMBANGAN EKOWISATA DENGAN LOCO TOUR DALAM UPAYA MENINGKATAN EKONOMI MASYARAKAT DI BLORA - Kristiani, Kristiani (MIIPS, 2010)
The purposes of this study are to reveal the natural potential to be developed as anatural tourist attraction, tours loco condition, condition of facilities, accessibility of naturaltourist attractions, tourist activities undertaken visiting tourists, business activities in the field of nature tourism that can improve the community economy , and Department policystrategies in developing Perhutani loco tour as an effort to increase tourism and conservation of natural teak forests in Blora.This research was based on the development and nature ekploratif with data collectiontechniques with questionnaires, in-depth interviews, participant observation, and analysis ofdocuments/archives. The validity of data the used peerdebriefing, triangulation of data andinformants review the analysis techniques with interactive models.Conclusions The study showed that the potential of existing natural potentialmaximum but not enough developed, condition loco tour, physically feasible for use as tourist transportation management but it is not managed properly, the condition and accessibility of support facilities have comprehensive facilities and many of fasilities are not well cared for and destroyed, tourists visiting just to see and enjoy nature tourism, local arts and local foods, as well as the lack of cooperation between loco tour manager in this case KPH Perhutani Department Cepu with District Government, Department of Tourism, private, and communities